Kohesi Teks Syair dalam Tunjuk Ajar Melayu Karya Tenas Effendy - Alber, Alber; Rahayu, Sri (GERAM, 2017)
Research on the cohesion of poetical text in Tunjuk Ajar Melayu by Tenas Effendy which viewed from the aspect of language. The role of cohesion is necessary in a text to support the linkage between the stanza with the stanza and the array with the array in a poem. With the cohesion will make it easier to read understand the author's intent. Cohesion can also affect the level of appreciation and understanding of the reader or the listener. Therefore, this study aims to know the cohesion between the lines in one line and antarbait in the text of the teachings of the teachings of Tenas Effendy Malay. The theory used Tarigan (1993), Effendy (2013), Tarigan (2009) and other supporting theories. Writing research this is descriptive-analitik with qualitative descriptive method. The data of this research are sourced Tunjuk Ajar Melayu by Tenas Effendy in 2013. Based on the research findings, there are several cohesion tools used in the text of lecture of Tenas Effendy's Malay teaching, among others, pronouncement, substitution, conjunction and lexical cohesion. There are several ways of lexical used are repetition, synonym and antonym and so on.